Serum immunoglobulins in multiple pregnancy. Issue 5 (May 1976) - Bryan, E M; Slavin, B; Nicholson, E
Abstract : The concentrations of immunoglobulins (Ig) G.A.M. and E were determined in paired umbilical cord and maternal sera in 50 twin pregnancies. Mean IgG levels were higher in cord than maternal sera and in most cases the cord IgG level related more closely to that of the other twin than to either maternal level or birthweight, and was in the range for singletons of the same gestational age. The three cases of fetofetal transfusion syndrome were exceptional in the large difference between IgG concentrations in recipient and donor twins. The discrepancy was much greater than that found between the levels of proteins produced by the fetus, suggesting a disturbance in maternofetal placental transfer. IgM was detected in all cord sera, with one exception, and the level was not related to order of birth. IgA was detected in 16% of cord sera, 13% in sera from first borns. IgE was detected in only 8% of cord sera and there was no evidence of placental transfer.